The intoxication of carbon tetrachloride of rats the lymph biochemical indexes (Experimental biology, 2016)
In this work the influence of carbon tetrachloride upon the lymph flow, biochemical content of lymph and plasma are studied. Carbon tetrachloride lead to the reduction in lymph flow and total protein content in the lymph and plasma. Shows the shift of the electrolyte composition of lymph and blood plasma.
Keywords: hydrocarbon; lymph; lymph nodes; blood plasma; electrolytes